Improved identification of viable myocardium using second harmonic imaging during dobutamine stress echocardiography. Issue 6 (1st December 2001) - Sozzi, F B; Poldermans, D; Bax, J J; Elhendy, A; Vourvouri, E C; Valkema, R; De Sutter, J; Schinkel, A F L; Borghetti, A; Roelandt, J R T C
Abstract : OBJECTIVE: To determine whether, compared with fundamental imaging, second harmonic imaging can improve the accuracy of dobutamine stress echocardiography for identifying viable myocardium, using nuclear imaging as a reference. PATIENTS: 30 patients with chronic left ventricular dysfunction (mean (SD) age, 60 (8) years; 22 men). METHODS: Dobutamine stress echocardiography was carried out in all patients using both fundamental and second harmonic imaging. All patients underwent dual isotope simultaneous acquisition single photon emission computed tomography (DISA-SPECT) with 99m technetium-tetrofosmin/ 18 F-fluorodeoxyglucose on a separate day. Myocardial viability was considered present by dobutamine stress echocardiography when segments with severe dysfunction showed a biphasic sustained improvement or an ischaemic response. Viability criteria on DISA-SPECT were normal or mildly reduced perfusion and metabolism, or perfusion/metabolism mismatch. RESULTS: Using fundamental imaging, 330 segments showed severe dysfunction at baseline; 144 (44%) were considered viable. The agreement between dobutamine stress echocardiography by fundamental imaging and DISA-SPECT was 78%, κ = 0.56. Using second harmonic imaging, 288 segments showed severe dysfunction; 138 (48%) were viable. The agreement between dobutamine stress echocardiography and DISA-SPECT was significantly better when second harmonic imaging was used (89%, κ = 0.77, p = 0.001 v fundamental imaging). CONCLUSIONS: Second harmonic imaging applied during dobutamine stress echocardiography increases the agreement with DISA-SPECT for detecting myocardial viability.